Pengaruh Electronic Word of Mouth dan Celebrity Endorsement Terhadap Purchase Intention dengan Brand Attitude sebagai Mediator pada Local Brand Cosmetics - Anis Aprillia Sari; Ida Bagus Nyoman Udayana; Agus Dwi Cahya (Ekonomis: Journal of Economics and Business, 2023)
The recent growth of beauty trends for facial and body care has gained a lot of attention. Furthermore, online reviews might make it easier for customers to purchase things. This makes the cosmetics industry grow rapidly, so their abilities must always be improved. Therefore, this study aims to test the influence of electronic word of mouth, celebrity endorsement, and brand attitude on purchase intention. This research is quantitative by taking 150 samples on consumers of Somethinc products in the Special Region of Yogyakarta. Sampling was carried out using a non-probability method and the sampling technique was purposive sampling. Data was collected through an online questionnaire link provided to responders. Data is analyzed using the SPSS application. According to the study's findings, the electronic word of mouth variable (X1) had a significant positive effect on brand attitude (Z). Furthermore, the celebrity endorsement variable (X2) had a significant positive effect on the brand attitude (Z), the brand attitude variable (Z) has a significant positive effect on the purchase intention (Y). Then, the electronic word of mouth variable (X1) had a significant positive effect on purchase intention (Y), and the celebrity endorsement variable (X2) had a significant positive effect on purchase intention (Y). In addition, the results of this study also showed that brand attitudes were able to act as a mediator in the influence of electronic word of mouth and celebrity endorsement on the purchase intentions of consumers of Something products in the Special Region of Yogyakarta.